First Language Use in English Language Teaching for Tourismat Politeknik Negeri Bali Jembrana - Mahardika, I Made Ojes; Manuaba, Ida Bagus (Badan Riset dan Inovasi Daerah Provinsi Bali, 2024)
Purpose: This study aims to identify why lecturers and students use (or do not use) Indonesian Language in the English language teaching-learning processes. Research methods: The study was conducted at Politeknik Negeri Bali Jembrana, which involved five lecturers and 64 students. The data are from the questionnaire which were analyzed quantitatively by quantifying the result of the questionnaire and finding the final score of the questionnaire. The result of the observation was analyzed qualitatively using the interactive data analysis. Results and discussion: The lecturers used the Indonesian Language in the teaching and learning process of EFL (English as a Foreign Language) in the form of code-switching, code-mixing, and interpreting, the lecturers use L1 in the teaching and learning process of EFL for instructional purposes, and both the students and the lecturers had a positive attitude toward the use of the Indonesian Language. Implication: Using L1 in the teaching and learning process of EFL can be done for instructional purposes, but lecturers need to consider students' English level mastery in deciding the use of L1 in the teaching and learning process of EFL.